Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Mismatch repair gene pathogenic germline variants in a population-based cohort of breast cancer - Tu Nguyen-Dumont; Jason A. Steen; Ingrid Winship; Daniel J. Park; Bernard J. Pope; Fleur Hammet; Maryam Mahmoodi; Helen Tsimiklis; Derrick Theys; Mark Clendenning; Graham G. Giles; John L. Hopper; et al. (Familial Cancer, 2020)

Disease-modifying drugs for multiple sclerosis and JC virus expression - Craig S. Miller; Sidney A. Houff; Jason Hopper; Robert J. Danaher; Julie A. Gurwell; Yushun Lin; Nubia Vega; Joseph R. Berger (Journal of NeuroVirology, 2012)

A Method for Setting the Size of Plant Conservation Target Areas - Mark A. Burgman; Hugh P. Possingham; A. Jasmyn J. Lynch; David A. Keith; Michael A. McCarthy; Stephen D. Hopper; Wendy L. Drury; Jason A. Passioura; Robert J. Devries (Conservation Biology, 2001)
Realistic time frames in which management decisions are made often preclude the completion of the detailed analyses necessary for conservation planning. Under these circumstances, efficient alternatives may assist in approximating the results of more thorough studies that require extensive resources and time. We outline a set of concepts and formulas that may be used in lieu of detailed population viability analyses and habitat modeling exercises to estimate the protected areas required to provide desirable conservation outcomes for a suite of threatened plant species. We used expert judgment of parameters and assessment of a population size that results in a specified quasiextinction risk based on simple dynamic models. The area required to support a population of this size is adjusted to take into account deterministic and stochastic human influences, including small‐scale disturbance, deterministic trends such as habitat loss, and changes in population density through processes such as predation and competition. We set targets for different disturbance regimes and geographic regions. We applied our methods to Banksia cuneata, Boronia keysii, and Parsonsia dorrigoensis, resulting in target areas for conservation of 1102, 733, and 1084 ha, respectively. These results provide guidance on target areas and priorities for conservation strategies.